Consumer’s behavior towards intention staying at a green hotel, Malaysia - Chong, Li Wen; Janny, Loi Wee Kee; Junaidi, Mohd Kurniah Ferry (2015)
Consumers nowadays are concern about eco-friendly environment and focus on the green product and service. This has been contributing many industries change their production trend to green product and service to meet the need and want of their customers. This also include impel the hotel going green. This current research is applying the theory of Planner Behaviour which developed by Ajzen to investigate the relationship of attitude, subjective norm and perceived behaviour control toward staying at a green hotel. This study surveyed 150 of respondents around Malaysia. A convenience sampling was selected because the sample was selected based on the personal judgment of the researcher. Online survey was used due to can cover wider geographical area and low budget. There were only 130 of respondents completed the questionnaire which mean 86.67% for the response rate. The results of the finding found that attitude, subjective norm and perceived behaviour control has significant relationship with the customers’ intention to stay at a green hotel. The limitation of study in this study was only covers the customers’ intention towards green hotel in Malaysia generally and size of sample might not comprehensive enough. The discussion of the finding include give some recommendation for future study and for hotel to improve themselves going to green hotel